DEVELOPMENT OF CROPPING PATTERN HYDROPONIC VEGETABLE MULTI COMMODITIES CONSIDERING DAILY WEIGHT AND HARVESTING AGE TO MAXIMIZE PROFIT - Iqbal Tawakkal, Muhammad
Increased public consumption of vegetables increases vegetable production (capacity and number of producers). There is an increase in demand for vegetables in the number and attributes of products such as packaging, brands, and product variants. Rumah Kebun Ibu (RKI) is a company engaged in the production and sale of hydroponic vegetable farming, located in Ngamprah District – West Bandung. RKI is currently collaborating with Amazing Farm (AF) and Borma for its hydroponic vegetable sales channel. AF requested a plant that weighs less than the specifications requested by Borma. For a pack of 250gr green pakcoy AF asks for 3-4 plants (weight 60-90 gr/plant), while Borma asks 2 plants (weight 100-120 gr/plant). For caisim AF asks for 5-7 plants per pack (30-45 gr/plant), while Borma asks 3-4 plants (50-65 gr/plant). This study aims to develop a multi-commodity hydroponic vegetable cropping pattern model with two types of product demand specifications that take into account plant weight and harvest age which can maximize profits using non-linear programming.. The calculation shows that the developed model can determine what commodities should be planted, the number of plants and the time of planting (harvesting age) in fulfilling the demand specifications of two types of markets to maximize profits. To achieve the target of the same amount of harvest weight, a larger plant weight (even though the number of plants is small) will be more profitable than a small plant weight (the number of plants is more).